Comparison of chemical composition of fruit pulp of Parkia biglobosa (Jacq.) Benth from differents ecoregions - Dao, Aboubacar Sidiki; Parkouda, Charles; Traoré, M.A. Esther; Guissou, Aimée W.D.B.; Vinceti, Barbara; Termote, Céline; Manica, Mattia; Bassolé, Imael Henri Nestor (Academic Journals, 2021)
Parkia biglobosa (Jacq.) Benth commonly called néré in French-speaking Africa is a semi-domesticated indigenous tree with a multi-purpose and highly appreciated use. Its pod-shaped fruits contain a yellowish floury pulp, eaten raw or used to make drinks, couscous and for raw or cooked dough. The objective of this study was to determine the profiles of minerals (Fe, K, Mg, Zn, Ca), beta-carotene, protein, ash, lipid and total sugar content as well as pH and acidity of the pulps from three ecoregions of Burkina Faso. The results showed quantitative difference in the composition of Parkia biglobosa (Jacq.) Benth pulp from the different ecoregions. Pulp from tree of South Sahelian zone contained the highest concentration of beta-carotene and carbohydrates 530.52±68.11 μg/100g; 64.96±8.9% DW, respectively. Whereas, the North Sudanian zone exceeded the others ecoregion in terms of K 3 301.25±872.85 mg/100 g DW; Mg 257.63±90.15 mg/100 g DW; Zn 1.28±0.37 mg/100 g DW; Ca (519.41±591.13 mg/100g DW) and protein 3.76±0.39 g/100 g DW. The South Sudanian zone displays the highest content in Fe (1.92±1.37 mg/100 g DW). As for the equivalent citric acid quantified in this study, the North Sudanian zone had the highest concentrations (0.96 ± 0.18 g/100 g DW) in the pulp. The observed variation has implications regarding the use of these data in food and nutrition programs, and in selecting sources of planting material for reforestation initiatives and agroforestry systems.